A movable feast: Ten millennia of food globalization - Kiple, Kenneth F (Cambridge University, 2013)
This book, based largely on The Cambridge World History of Food, provides a look at the globalization of food from the days of the hunter-gatherers to present-day genetically modified plants and animals. The establishment of agriculture and the domestication of animals in Eurasia, Africa, the Pacific, and the Americas are all treated in some detail along with the subsequent diffusion of farming cultures through the activities of monks, missionaries, migrants, imperialists, explorers, traders, and raiders.